If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + (y + -14) = 0 Reorder the terms: 3 + (-14 + y) = 0 Remove parenthesis around (-14 + y) 3 + -14 + y = 0 Combine like terms: 3 + -14 = -11 -11 + y = 0 Solving -11 + y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + y = 0 + 11 Combine like terms: -11 + 11 = 0 0 + y = 0 + 11 y = 0 + 11 Combine like terms: 0 + 11 = 11 y = 11 Simplifying y = 11
| -28x+29x=16+28 | | 20k+90=10k+20 | | 5x+2(4x-8)=200 | | 0.12x+0.3(x-4)=0.01(2x-7) | | 5(34)/1000 | | 4m/5=-10 | | 6x+1=2x | | 10y-25=3y+3 | | -3+4m=-55 | | 23n-55=3n-35 | | 2(x+1)=27 | | 7(9+k)=74 | | x^3-5x=56 | | (2x^4y)(-3x^2y^3)= | | 4=18-2v | | X=5/4(-12/5) | | 4+4z-2=8z+10-2z | | (3X^2)(6X^5)/2X^3 | | 9(.3333333333x)=3x | | (2x^4y)(-3x^2y^3)=6 | | v=24+74 | | -0.10(76)+0.90x=0.05(x-16) | | 5/4(-12/5) | | -7=-9/5-1 | | x+6+9= | | Ln(8)=2x | | 3.18+2.6+0.9x+x=28 | | (x^(5/3))-2x=0 | | -1/2x=18/5 | | 7(4x)-y+3x= | | 1+10d+4d= | | 5/4y-5y=9 |